2019
DOI: 10.2147/ott.s212340
|View full text |Cite
|
Sign up to set email alerts
|

<p>Establishment of reference intervals for serum [−2]proPSA (p2PSA), %p2PSA and prostate health index in healthy men</p>

Abstract: Background Prostate cancer (PCa) is the second most common cancer among men worldwide. Recent research has identified [−2]proPSA (p2PSA), %p2PSA and prostate health index ( phi ) as new biomarkers for the early diagnosis and grading of PCa. However, few studies have used these parameters in a healthy population. In this study, we aimed to establish reference intervals (RIs) for p2PSA, %p2PSA and phi in healthy men based on age stratification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
3
0
1
Order By: Relevance
“…The width of the interval increased with age. This was mainly attributed to the increasing upper limit of the reference range with age, an observation in concordance with what has been reported earlier in several studies conducted on large number of people of various ethnic backgrounds 15 20 .
Figure 2 The reference range of the disease for each age.
…”
Section: Resultssupporting
confidence: 91%
“…The width of the interval increased with age. This was mainly attributed to the increasing upper limit of the reference range with age, an observation in concordance with what has been reported earlier in several studies conducted on large number of people of various ethnic backgrounds 15 20 .
Figure 2 The reference range of the disease for each age.
…”
Section: Resultssupporting
confidence: 91%
“…Three of these could not be retrieved [17] , [18] , [19] . Sixty-five studies [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , reported in 69 articles [20] , [21] ,…”
Section: Evidence Synthesisunclassified
“…Included studies involved 34 287 men, 14 792 (43.14%) diagnosed with PCa and 7905 (23.06%) with csPCa. Not all studies included PSA-selected patients [23] , [25] , [78] , [84] , [87] , [27] , [34] , [35] , [36] , [37] , [40] , [53] , [74] . The selection criteria and main characteristics of participants are summarized in Table 2 .…”
Section: Evidence Synthesismentioning
confidence: 99%
“…However, recent studies have revealed that no biomarker alone is sufficient in diagnosis and a multivariable diagnostic approach is more eligible [5,8,9]. Nevertheless, due to some disadvantages of these markers, the free prostate-specific antigen/total prostate-specific antigen (free PSA/total PSA) ratio has become the most frequently used value in clinical practice [9,10]. Recently, it has been reported in the literature that the free PSA/total PSA ratio is more significant than PSA alone in differentiating prostate cancer and BPH in patients with serum total PSA levels between 4.0 and 10.0 ng/mL [11,12].…”
Section: Introductionmentioning
confidence: 99%